Assessing the digital readiness of the residents in MacArthur, Leyte for e-wallet adoption - Guarino, Angeline B.; Mancol, Aldrin M.; Guitoria, Mark Noel M.; Jose, Roanne M.; Ocasla, Kely Mae B.
E-wallets have become a bridge to financial inclusion, allowing individuals without traditional bank accounts to participate in the digital economy. However, despite many initiatives leading the efforts to drive the Philippines toward a cashless economy, rural areas still face challenges due to socio-economic, infrastructural, and technological barriers. The lack of studies about e-wallet adoption in rural areas makes them underrepresented because of existing studies that mainly focus on urban settings or the general population. To address this gap, the study was conducted among 152 participants aged 20-34 years old, all residents of MacArthur, Leyte, a fourth class municipality. The study employed a quantitative approach using a 5-Likert scale to gather data, which was analyzed through weighted means and standard deviation. The results showed a significant level of digital readiness among the residents of MacArthur, Leyte, indicating a high level of openness to e-wallet adoption. However, the community needs to improve its technological and infrastructural capacity, as these, along with socio-economic factors, continue to hinder wider adoption. Additionally, consumer feature preferences, particularly ease of use, security, and customer support, along with frequent usage for bills payment, mobile load, and money transfers, were found to significantly influence e-wallet adoption decisions. The study intends to contribute to understanding the specific factors that influence the adoption of digital financial tools in rural areas, with the goal of developing policy strategies to enhance digital readiness and foster greater financial inclusion in MacArthur, Leyte.